Potencial da palma forrageira (Opuntia ficus-indica) na perspectiva da inovação frugal como cultura alternativa não convencional : prospecção tecnológica de espécie exótica - Santos, Maria de Fátima Rufino dos (2021)
Due to the economic context demarcated by deep inequality, facing severe restrictions in budget terms, Brazilian society has been looking for alternatives so that its reality can be transformed. The study of agricultural cultures, even if exotic, has generated new knowledge and favored the proposition of projects with positive socioeconomic potential. One of these efforts has been associated with Non-Conventional Food Plants (PANCs), which are currently very appreciated – case of Forrage Palm, an exotic species, rich in bioactive components and different nutrients, cultivated mainly in the Northeast region of Brazil. Therefore, this study considers the Foraging Palm, from the perspective of frugal innovation, in its social, environmental and economic dimensions, using tools and instruments of technological prospecting in a systematic way, envisioning its indication as a Non-Conventional and Sustainable Alternative Culture (CANCS) capable of implementation in another region as new ventures, income generators. The results obtained show that the Foraging Palm is a species that presents different aggregate potentialities, susceptible to sustainable cultivation, use and exploitation in the extreme north of Brazil.